The metaphysics of hyperspace - Hudson, Hud (OUP E-Books., 2005)
Hud Hudson offers an examination of philosophical reasons to believe in hyperspace. He explores non-theistic reasons, then inquires into a variety of puzzles in the metaphysics of material objects that are generated by the hypothesis of hyperspace or informed by it. Finally, he explores theistic reasons.